Implementasi Komparasi Algoritma Klasifikasi Menentukan Kelulusan Mata Kuliah Algoritma Universitas Budi Luhur - Nahot Frastian (STRING (Satuan Tulisan Riset dan Inovasi Teknologi), 2018)
The implementation of algorithm comparison provides innovation and motivation to students every semester of lecture. Budi Luhur University students attending all learning activities or face-to-face meetings in the classroom for each subject will have more chance to pass compared with those who rarely present. Some lecturer's evaluation to give a pass in subject include attendance, assignment, midterm examination and final examination. In this research, when creating an appropriate algorithm to determine the pass in subject of the students, this researcher will use data mining classification technique with 3 methods of Classification algorithm, namely Algorithm C4.5 (decision tree), Naïve Bayes and Random Forest with result labels of fail and pass. The results of the research tested by using the same dataset on the 3 algorithms through comparison get the value of AUC and Confusion Matrix, obtain the value of Area Under Curve (AUC) of 2,000 from the Naïve Bayes model, while the greatest Accuracy or Confusion Matrix values is in the C4.5 algorithm (decision tree) with a value of 98.88%. Thus, the algorithm subject gives an assessment of the C4.5 algorithm (decision tree). The implementation of classification algorithm comparison determines a pass in algorithm subject at Budi Luhur University.